177Lu‐Gold Nanohybrids in Radiotherapeutic Approaches Against Cancer - Mathilde Ponchelle; Marek Pruszyński; Edmond Gravel; Eric Doris (Small Science)
Internal radionuclide therapy using lutetium‐177 (177Lu)‐based radiopharmaceuticals has emerged as a promising approach in the field of nuclear medicine and oncology. Combining the radioactive lanthanide with high atomic number metal nanoparticles such as gold potentiates the radiotoxicity of lutetium by an amplification process. 177Lu‐gold nanohybrids have been investigated by various research groups, both in vitro and in vivo, to decipher the physicochemical, radiochemical, and biological factors that would enable selective and optimal dose deposition in tumors. This review focuses on 177Lu‐gold tailored approaches that are developed in the literature to locally enhance internal radiotherapeutic effects.